Evidence-Based Endocrine Surgery (Springer Singapore, 2018)
In this textbook, leading experts from highly acclaimed institutions describe evidence-based best practice in the management of a wide range of benign and malignant thyroid, parathyroid, adrenal, and neuroendocrine conditions. Detailed attention is devoted to the current role of surgery, including minimally invasive surgery and robotic surgery, in different endocrine disorders. The reader will also learn how best to respond to the problems that may be encountered during endocrine surgical practice. While much of the focus is on surgical aspects, the approach is multidisciplinary, with inclusion of information on recent advances in epidemiology, genetics, cytology, pathology, imaging modalities, and other treatment options. The clear text is complemented by instructive clinical cases as well as numerous high-quality illustrations and tables summarizing key points. This book will be of value for specialists in endocrine medicine and surgery as well as general surgeons with an interest in endocrine surgery.